Peran Ulama dalam Pengembangan Intelektual Tamadun Melayu (Studi Kasus Abad ke-18) - Aulia, Azikri; Ritonga, Afrida; Saiful, Adek; Khoirani, Suci (Journal of Practice Learning and Educational Development, 2026)
Scholars played a central role in the intellectual development and civilization of Islam in the Malay region, particularly in the 18th century, which was marked by intensified scientific activities, writing, and cross-regional intellectual networks. This article aims to examine the role of scholars in the intellectual development of Malay civilization in the 18th century through their contributions in the fields of education, Islamic writing, and the formation of scientific networks between the Malay world and the Middle East. This study uses a qualitative approach with library research methods, with data sources in the form of classical manuscripts, books by Malay scholars, and relevant historical literature. Data analysis was conducted through a historical approach and content analysis of the scholars' works. The results of the study show that 18th-century scholars not only played a role as educators and disseminators of Islamic teachings, but also as agents of intellectual transformation who shaped the Malay scholarly tradition based on the integration of religious knowledge, language, and local culture. The contributions of these scholars became an important foundation for the development of Malay civilization and the continuity of the Islamic intellectual tradition in the archipelago.